1998
DOI: 10.1037/0012-1649.34.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Overt and relational aggression in Russian nursery-school-age children: Parenting style and marital linkages.

Abstract: Maternal and paternal parenting styles and marital interactions linked to childhood aggressive behavior as described in Western psychological literature were measured in an ethnic Russian sample of 207 families of nursery-school-age children. Results corroborated and extended findings from Western samples. Maternal and paternal coercion, lack of responsiveness, and psychological control (for mothers only) were significantly correlated with children's overt aggression with peers. Less responsiveness (for mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
256
5
16

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(293 citation statements)
references
References 60 publications
16
256
5
16
Order By: Relevance
“…Clearly the next step in a program of research intended to continue to elucidate the ways in which correspondence in parenting between both parents in the home influences child development would be to link parental (dis)agreement on actual and perceived parenting practices and specific developmental outcomes for the child. Although no links between the PSDQ and child outcomes are shown here, it is important to note that other work has clearly shown that the parenting dimensions tapped by the PSDQ are linked with theoretically relevant child outcomes (Coolahan et al, 2002;Hart et al, 1998Hart et al, , 2000Russell et al, 2003;Yang et al, 2004).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Clearly the next step in a program of research intended to continue to elucidate the ways in which correspondence in parenting between both parents in the home influences child development would be to link parental (dis)agreement on actual and perceived parenting practices and specific developmental outcomes for the child. Although no links between the PSDQ and child outcomes are shown here, it is important to note that other work has clearly shown that the parenting dimensions tapped by the PSDQ are linked with theoretically relevant child outcomes (Coolahan et al, 2002;Hart et al, 1998Hart et al, , 2000Russell et al, 2003;Yang et al, 2004).…”
Section: Discussionmentioning
confidence: 83%
“…Although this measure is used frequently in the literature and has been adapted now for effective use in multiple cultural settings, including Russia (Hart, Nelson, Robinson, Olson, & NcNeilly-Choque, 1998), China (Wu et al, 2002) and African-American Head Start communities (Coolahan, McWayne, Fantuzzo, & Grim, 2002), most investigators have only used the self-report feature and have not exploited the spousal report feature. In order to reduce the total number of analyses conducted with this small sample, only the three overall scales for authoritativeness, authoritarianism, and permissiveness were used in the analyses below.…”
Section: Procedure/measuresmentioning
confidence: 99%
“…Moreover, research has consistently demonstrated associations between parental psychological control, which seeks to undermine children's autonomy, and children's aggressive behaviors within the peer context (Hart et al 2003;Nelson and Crick 2002;Rogers et al 2003). With regard to relational aggression specifically, parental enmeshment (in the form of excessive maternal coercion) has been found to be associated with greater perpetration of relational aggression in a sample of Russian nursery-school-age children (Hart et al 1998), and parental psychological control has been significantly linked to increased relational aggression in pre-school age Chinese girls (Nelson et al 2006). Such research, though limited to younger children and peer relationships, suggests that difficulties with autonomy and enmeshment in early adolescent peer relationships may also serve as precursors to the development of relational aggression in later romantic relationships.…”
Section: Developmental Significance Of Autonomy In Adolescencementioning
confidence: 98%
“…The findings of a number of studies reveal an association between the quality of parenting styles and children's behavioural problems (Anthony et al, 2005;Aunola & Kurmi, 2005;Chang, Schwartz, Dodge, & McBride-Chang, 2003;Hart, Nelson, Robinson, Olsen, & McNeilly-Choque, 1998;Henderson, Dakof, Schwartz, & Liddle, 2006;Mulvaney & Mebert, 2007;Raboteg-Šarić, Rijavec & Brajsa-Zganec, 2001; Russell, Hart, Robinson & Olsen, 2003;Stevens, Vollebergh, Pels, & Crijnen, 2007). More specifically, Barnes and Farrell (1992) found that parenting styles were significant predictors of behavioural problems, suggesting that positive parenting techniques such as high level of parental support and monitoring tended to have children who were less likely to exhibit drink problems, drug use, misconduct at school and deviant behaviour in general.…”
Section: Introductionmentioning
confidence: 99%